Латышские глаголы на -ēt: семантика vs. спряжение - Дубасова, Анжелика (Vilnius University Open Series, 2021)
The conjugation of secondary Latvian verbs is determined with high accuracy by their suffixes. However, verbs with the suffix -ē- are different: they are more or less equally divided between the traditional second and third conjugations. The article sets out to prove or disprove the hypothesis that the assignment of Latvian verbs with the suffix -ē- to a specific conjugation correlates with their semantics. For that purpose, 705 disyllabic verbs ending in -ēt were collected and marked by their origin, transitivity, and conjugation. Verbs that are not obvious borrowings were then divided into semantic classes. As a result of the semantic classification, the working hypothesis was confirmed: second conjugation verbs ending in -ēt predominantly denote agentive actions (creation, destruction, modification, etc.), whereas third conjugation verbs usually denote phenomena, processes, states, and sound production. The results suggest that the Latvian verbal system exhibits a close interrelation between semantics and morphology.